2022
DOI: 10.1507/endocrj.ej21-0492
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum C-peptide-releasing effects and the risk of elevated uric acid in type 2 diabetes mellitus

Abstract: Our study aimed to investigate the C-peptide-releasing effect associated with the risk of elevated serum uric acid (SUA) levels in patients with type 2 diabetes mellitus (T2DM). In the cross-sectional study, 345 patients with T2DM hospitalized at the First Affiliated Hospital of Harbin Medical University were consecutively enrolled, and their baseline data were collected. The study design used two parameters for C-peptide releasing effects: the multiplication effect of 1 h postprandial C-peptide to fasting C-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
1
1
Order By: Relevance
“…Our findings showed the non-linear relationship between them, indicating that in a proper range, the renal impairment incidence did not rise with the increment of UA levels. Additionally, the previous studies had indicated that fasting C-peptide was significantly associated with UA in patients with T2DM ( 31 , 32 ), however, no multiplication interaction effect between these two clinical factors for the renal dysfunction odds was found in the present study.…”
Section: Discussioncontrasting
confidence: 75%
“…Our findings showed the non-linear relationship between them, indicating that in a proper range, the renal impairment incidence did not rise with the increment of UA levels. Additionally, the previous studies had indicated that fasting C-peptide was significantly associated with UA in patients with T2DM ( 31 , 32 ), however, no multiplication interaction effect between these two clinical factors for the renal dysfunction odds was found in the present study.…”
Section: Discussioncontrasting
confidence: 75%
“…Increased serum uric acid (SUA) is associated with diabetes [5] and several diabetic complications [6][7][8][9][10][11][12] including diabetic peripheral neuropathy (DPN). Indeed, hyperuricemia is common in patients with T2DM and associated with the C-peptide incremental effect of islet beta cell function in T2DM, especially in female patients [13]. Except for diabetes itself, SUA levels are higher in T2DM patients with DPN than those without DPN [14,15].…”
Section: Introductionmentioning
confidence: 99%